The Effect of conjugated linoleic acid (CLA) on inflammatory factors in Non-Alcoholic Fatty Liver Disease (NAFLD): A randomized controlled clinical trial - Abedi, Ranasadat; Aref-Hosseini, Seyed-Rafi; Khoshbaten, Manouchehr; Ebrahimi-Mameghani, Mehrangiz; Jamali Laleh, Haleh; Jalalypour, Farzaneh; Kabir Mamdouh, Bita (Progress in Nutrition, 2018)
The worldwide alarming increase of non-alcoholic fatty liver disease (NAFLD), leads to advent of wide range of therapeutic strategies. As a functional supplement, conjugated linoleic acid (CLA) is related to weight loss and improves histology parameters of inflammatory markers patients with NAFLD. The aims of this study were to investigate the effects of CLA in company with vitamin E on body composition as well as inflammation by evaluating anthropometric parameters and the serum level of liver enzymes and inflammatory factors in NAFLD patients. In a randomized single-blind controlled trial with two subgroups, 54 obese patients with NAFLD randomized to consume supplement with either three softgel capsules of CLA (80% softgel ,1000mg) in company with one softgel capsule of vitamin E (400 IU) (CLA group) or one softgel capsule of Vitamin E (control group), daily for eight weeks. All the participants were asked to maintain their prescribed diet and usual lifestyle habits. Body composition was assessed at the beginning and end of the study using bioelectrical impedance analysis (BIA). At the end of the study, fat mass (P=0.001), muscle mass (P=0.023) and total body water (P=0.004) were significantly better in CLA group. The mean values of tumor necrosis factor (TNF)-α, interleukin (IL)-6, high sensitivity C-reactive protein (hs-CRP) and serum alanine aminotransferase/aspartate aminotransferase (ALT/AST) ratio were significantly decreased in CLA group. Also; ALT/AST ratio (P=0.046) and TNF- α (P=0.001) showed a statistically significant decrease compared to the control group. Besides, the CLA group demonstrated significantly increased levels of interleukin (IL)-10. Considering the vital role of inflammation in progression of NAFLD, our results suggest that CLA could be a promising supplement in NAFLD treatment.